A robust cocatalyst Pd4S uniformly anchored onto Bi2S3 nanorods for enhanced visible light photocatalysis. Issue 8 (21st January 2015) - Long, Lu-Lu; Zhang, Ai-Yong; Huang, Yu-Xi; Zhang, Xing; Yu, Han-Qing
Abstract : A novel photocatalyst hybrid, Bi2 S3 nanorods uniformly anchored by Pd4 S nanoparticles, was successfully synthesized using a facile method for efficient visible light photocatalysis. Abstract : Pd4 S is one of the main poisoning products of metallic Pd catalysts, caused by hydrogen sulfide, and its catalytic applications have not been given sufficient attention. Herein, a novel photocatalyst hybrid, Bi2 S3 nanorods uniformly anchored by Pd4 S nanoparticles, was successfully synthesized using a facile method and used for efficient visible light photocatalysis. Pd4 S nanoparticles were formed in situ from the Bi2 S3 nanorods through thermal reduction, and played an important role in the enhanced overall performance of this hybrid. The as-prepared Pd4 S/Bi2 S3 heterostructure exhibited superior electrochemical and photochemical properties and had a higher photocatalytic activity in the degradation of atrazine, a typical herbicide found in the environment, compared to both Pd4 S and Bi2 S3, individually. The uniformly dispersed Pd4 S nanoparticles, substantially facilitate charge separation and transfer on the Bi2 S3 nanorods, and then serve as active sites, leading to excellent photocatalytic capacity.